ANALYSIS SMART SUPPLY CHAIN (SSC) AND SUPPLY CHAIN RESILIENCE IN SUPPORTING SMART TECHNOLOGY AND ITS IMPACT ON OPERATIONAL PERFORMANCE ON A GEOTHERMAL COMPANY - Ismail, Ismail; Surjasa, Dadang (International Journal of Business Studies, 2024)
This research aims to analyze the influence smart supply chain to operational performance, supply chain resilience and smart technologies as well as roles smart technologies in mediating influence smart supply chain to operational performance and moderate supply chain resilience to operational performance at a geothermal company. The sampling design used in this research is non-probability sampling with technique purposive sampling. The processed data came from 242 respondents and then analyzed using Structural Equation Modelling (SEM) method. The research found that smart supply chain positive influence on operational performance, supply chain resilience and smart technologies, Supply chain resilience has positive influence on smart technologies and operational performance and smart technologies has positive influence on operational performance. The research results found smart technologies able to mediate the influence of smart supply chain to operational performance but not able to moderate the influence supply chain reselience to operational performance. This study shows that operational performance can be maximized and optimized using smart supply chain technologies to support implementation smart technology. .